Association between allergic conditions and school absenteeism among Indian adolescents - Qian, Tina; Deprato, Andy; Debnath, Smriti; Haldar, Prasun; Chattopadhyay, Dwiptirtha; Garcia‐Aymerich, Judith; Annesi‐Maesano, Isabella; Patel, Neel; Lacy, Paige; Moitra, Saibal; Moitra, Subhabrata (Clinical and experimental allergy, 2024)
Previous studies on allergic conditions and school absenteeism are limited and have only focused on asthma.Our research relating allergic conditions with school absenteeism highlight the much-undermined social burdens of allergic conditions.